Contribution of Fourier‐domain optical coherence tomography to the diagnosis of keratoconus progression. Issue 2 (February 2019) - Ouanezar, Sofiane; Sandali, Otman; Atia, Raphael; Temstet, Cyrille; Georgeon, Cristina; Laroche, Laurent; Borderie, Vincent; Bouheraoua, Nacim
Abstract : Purpose : To determine the anatomic criteria for diagnosing keratoconus progression by corneal optical coherence tomography (OCT). Setting : Quinze‐Vingts National Ophthalmology Hospital, Paris, France. Design : Prospective case series. Methods : Scanning‐slit corneal topography (Orbscan II) and Fourier‐domain corneal OCT (RTVue) were performed in eyes with mild to moderate keratoconus (progressive or nonprogressive [stable] ectasia) at each examination to assess the keratoconus. Disease progression was defined as an increase of at least 1.0 diopter (D) in the steepest keratometry (K) measurement over 6 months. Results : Of the 134 eyes of 134 patients with mild to moderate keratoconus, 98 had had progressive ectasia and 36 nonprogressive ectasia. The mean maximum K increased significantly in the progressive group (2.1 D ± 1.2 [SD], P < .0001) and remained constant in the stable group (−0.03 ± 0.39 D, P = .31). The mean thinnest corneal thickness increased significantly in the progressive group (−7.98 ± 9.3 μm, P < .0001) and remained constant in the stable group (−0.52 ± 4.21 μm, P = .22). The change in maximum K was significantly correlated with changes in the thinnest corneal thickness ( r = −0.61, P < .0001). A cutoff value of −5 μm for the change in thinnest corneal thickness was identified on receiver operating characteristic curves as a threshold separating cases of progressive and stable keratoconus (area under the curve, 0.79; sensitivity, 68%; specificity, 89%). Conclusions : Topographic data partly reflected the structural changes occurring during the progression of corneal ectasia. Based on the pachymetric parameters provided by OCT, corneal and epithelial thinning was correlated with corneal deformation. The use of corneal OCT might therefore improve the diagnostic sensitivity for keratoconus progression.